2002
DOI: 10.1080/10611860290031868
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Administration to Rabbits of Non-stealth and Stealth Doxorubicin-loaded Solid Lipid Nanoparticles at Increasing Concentrations of Stealth Agent: Pharmacokinetics and Distribution of Doxorubicin in Brain and Other Tissues

Abstract: The pharmacokinetics and tissue distribution of doxorubicin incorporated in non-stealth solid lipid nanoparticles (SLN) and in stealth solid lipid nanoparticles (SSLN) (three formulations at increasing concentrations of stearic acid-PEG 2000 as stealth agent) after intravenous administration to conscious rabbits have been studied. The control was the commercial doxorubicin solution. The experiments lasted 6 h and blood samples were collected at fixed times after the injections. In all samples, the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(69 citation statements)
references
References 23 publications
2
67
0
Order By: Relevance
“…SLN have been intensively investigated for dermal application, 4 parenteral 5,6 and peroral 7,8 administration, and ocular delivery. 9 However, only one article has been published to date for the use of SLN in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…SLN have been intensively investigated for dermal application, 4 parenteral 5,6 and peroral 7,8 administration, and ocular delivery. 9 However, only one article has been published to date for the use of SLN in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…There was always less doxorubicin in the liver, lungs, spleen, heart and kidneys after injection of any of the types of SLNs than after the doxorubicin solution. In particular, all SLNs formulations significantly decreased heart and liver concentrations of doxorubicin [79]. Interestingly, both non-coated and coated SLNs showed a similar low uptake by liver and spleen macrophages [80].…”
Section: Anthracyclinesmentioning
confidence: 91%
“…The same study design, repeated in healthy rabbits, showed similar pharmacokinetic behavior and tissue distribution parameters. [43] Docetaxel-incorporated albumin-lipid nanoparticles (DNPs) in vitro induce apoptosis of several cancer cell lines, and in vivo, accumulate at the experimental glioma site. [44] This phenomenon is believed to be due to EPR effect.…”
Section: Preclinical Studies In Brain Tumorsmentioning
confidence: 99%